340 Experience of the use of laparoscopic resectability index in patients with advanced ovary epithelial carcinoma in the instituto nacional de cancerologia. Bogota, colombia. (18th September 2019) - Torres, J; Rodriguez, J; Calderon, P; Santana, D; Suescun, O; Acosta, J
Abstract : Objectives: Describe the experience of the laparoscopic resectability index (Fagotti score) to define primary cytoreduction versus neoadjuvant chemoterapy in patients with suspected advanced ovarian cancer from January 2017 to February 2019. Methods: Descriptive, retrospective study. Patients with stage III-IV advanced ovarian epithelial cancer were included. Clinical, histopathological and surgical variables related to the procedure were analyzed. An univariate analysis was performed in the statistical program SPSS version 21. Results: 14 cases are presented. The mean age was 58 years (+/- 8.2). 12 patients had stage IIIC and 2 stage IV. All were serous histological type, with 85.7% of high grade. The mean BMI was 24 (±3.4). All patients had ECOG between 0 and 1. In 85.7% of the cases the computed tomography was the preoperative image of choice.The score was ≥ 8 in 64% of the cases and <8 in 36%. In this last group, complete primary debulking was achieved in the same surgical time. The median time was 157 minutes (60–540), the median bleeding was 50 cc (5–2000). The median hospital stay was 2 days (1–14). There were no intraoperative complications in the first 30 days. There were 2 deaths not associated with the procedure. These were secondary to atrial fibrillation and pleural effusion. Conclusions: The laparoscopic resectability index is a useful tool to define the primary treatment in patients with advanced ovarian cancer, with low morbidity in our institution. It is necessary to perform prospective validation of these results.